2021
DOI: 10.1038/s41564-020-00830-7
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage-resistant Acinetobacter baumannii are resensitized to antimicrobials

Abstract: Carbapenem-resistant Acinetobacter baumannii is responsible for frequent, hard-to-treat and often fatal healthcare-associated infections. Phage therapy, the use of viruses that infect and kill bacteria, is an approach gaining significant clinical interest to combat antibiotic-resistant infections. However, a major limitation is that bacteria can develop resistance against phages. Here, we isolated phages with activity against a panel of A.baumannii strains and focused on clinical isolates AB900 and A9844 and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
174
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(185 citation statements)
references
References 67 publications
9
174
2
Order By: Relevance
“…been observed for bacterial pathogens of fish and moths, has been modeled in A. baumannii, and has been inferred with V. cholera in humans (24)(25)(26)(27)(28)(29)(32)(33)(34). To assess virulence in our isolated resisters, we tested their growth ability in media that simulated the host microenvironment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…been observed for bacterial pathogens of fish and moths, has been modeled in A. baumannii, and has been inferred with V. cholera in humans (24)(25)(26)(27)(28)(29)(32)(33)(34). To assess virulence in our isolated resisters, we tested their growth ability in media that simulated the host microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…Further, these studies are largely limited to pathogens with nonmammalian hosts. One exception is by Altamirano et al (29), who found a loss of virulence in phage-resistant A. baumannii in a murine infection model. The other exception is by Seed et al (27), who found loss of virulence in some Vibrio cholerae strains isolated from cholera patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Denes et al (2015) revealed that mutations associated with phage resistance in Listeria monocytogenes were found primarily in two loci, which link to phage adsorption. The phage resistant mutants of Acinetobacter baumannii had a single-nucleotide deletion resulting in a frameshift in a gene within the K locus (Gordillo Altamirano et al, 2021). Another lytic phage SPO1 could gain a broader host range against Bacillus subtilis after having mutations in two genes, encoding the baseplate, and the fiber proteins required for host attachment (Habusha et al, 2019).…”
Section: Introductionmentioning
confidence: 99%